Yo Frankie! the Apricot Open Game project ([Amsterdam, the Netherlands] Blender Foundation, 2010)
"Yo Frankie!" is a 3D game about a pesky rodent who's biggest Joy is to tease the other animals, annoy the crap out of everyone and even ruthlessly destroy innocent forest life!
DVD
The game is based on the evil flying squirrel from the 3D short movie Big Buck Bunny, which is included on this DVD as well.
"Yo Frankie!" is the result of the Apricot Open Game project, the third Open Project by the Blender Foundation to validate, test and improve open source software for 3D game creation. Six artists and developers have worked for a half year in the Amsterdam Blender Institute to realize this project.
The two main programs used for this project were the 3D creation suite Blender and the 3D game engine Crystal Space.
Yo Frankie! DVD contains: A full functional game in the Blender Game Engine, running in Linux, Windows and OS X. A complete level in Crystal Space, with installer, running in Linux, Windows and OS X. All .blend files, models, textures, sound clips, game sources, and so on... all the material used to create the gtame. Documented and video tutorials by the team members about all technical aspects the game; like how to re-use assets, animate characters, or add new levels.
Keywords: Video games; Video games -- Design